L’état des lieux de l’intelligence économique en France, exploration par la méthode « color insight ». (Étude jusqu’à 2018): The state of economic intelligence in France, exploration by the “color insight” method. (Study until 2018) - Mohand Amokrane BELKACEMI; Felana RABEKOLO (Journal of North African Economies, 2025)
In the face of economic war and the current international context, economic intelligence is the right tool to survive. It enables various actors – states, territories and companies – to collect information, and use them to act, to protect themselves against internal and external attacks and to make influence in order to direct any decisions in their favor. The first report on economic intelligence in France took place in 1994, the Martre report (Martre, 1994), which remains highly regarded in this field. A quarter of a century has passed since the publication of the Martre report. We found very useful to study the evolution of economic intelligence at the national level in France by conducting field research and cross-referencing the data collected with other studies to support our research results.